Soil and Groundwater Contamination Based on Geological and Hydrogeological Investigation - BARKAH, MOCHAMAD NURSIYAM; hadian, mohamad sapari dwi; Suganda, Bombom Rahmat; Iskandarsyah, Teuku Yan Waliyana Muda; Frini, Gisca Gia; Nadzif, Nor Farina (Journal of Geological Sciences and Applied Geology, 2017)
Water and environment are different things but they have a close relation each other. One of area in Indonesia Site ‘X’ (confidential site) has rapid development and many industries have built up their business here. The main issue is about the condition of soil and groundwater in this area are become contaminated in their waste disposal which is near with the resident area. Purposed of the study is to know how deep and extent the level of contamination in soil and groundwater. The investigations are using soil assessment, monitoring well installation, and aquifer testing. The soil assessment is using standard traditional drilling such as split spoon for subsurface drilling and sampling. Split spoon logging technique is more detail and provide good sampling for vertical or angle soil boring. Angle soil boring was done to know the detail soil sampling data near the resident area. Based on geological data, there are twelve soils boring (ten soils boring and two monitoring wells). The soil investigation observed as very fine grained to depths the recorded water table with coarser fine grained soil as depth. The indication of pure solvent was observed in three central location soil boring based on soil sampling. The PID (Photo-Ionization Detector) reading indicate that the soil sampling >1,000 ppm and with evident of solvent/hydrocarbon odour was indicating as impacted samples.  Based on hydrogeology data, there are eleven monitoring wells (two the newest MW and nine the existing MW). This research area has shallow aquifer system at depths 8.0-10.0 meter below groundwater surface as an unconfined aquifer layer. The monitoring well installation was observed five impacted monitoring wells. From one to five well, there is one well can looks clearly the sheen and has strong solvent based on laboratory in one monitoring well.Based on the data analysis, discovered that the research area was impacted. The collected data bring us to the next step that the research area should be remediated to make our environment clean or decreasing the level of contamination concentrate. Additionally, soil and groundwater contaminant levels have likely eliminated the previous remedial alternative suggestion of slow release oxygen and along with the soil geological conditions and severely reducing groundwater conditions, will make all remedial efforts challenging.